Stimulatory Role of SPAK Signaling in the Regulation of Large Conductance Ca2+-Activated Potassium (BK) Channel Protein Expression in Kidney - Bi, Ye; Li, Chunmei; Zhang, Yiqian; Wang, Yunman; Chen, Shan; Yue, Qiang; Hoover, Robert S.; Wang, Xiaonan H.; Delpire, Eric; Eaton, Douglas C.; Zhuang, Jieqiu; Cai, Hui (Frontiers in Physiology, 2020)
SPS1-related proline/alanine-rich kinase (SPAK) plays important roles in regulating the function of numerous ion channels and transporters. With-no-lysine (WNK) kinase phosphorylates SPAK kinase to active the SPAK signaling pathway. Our previous studies indicated that WNK kinases regulate the activity of the large-conductance Ca2+-activated K+ (BK) channel and its protein expression via the ERK1/2 signaling pathway. It remains largely unknown whether SPAK kinase directly modulates the BK protein expression in kidney. In this study, we investigated the effect of SPAK on renal BK protein expression in both HEK293 cells and mouse kidney. In HEK293 cells, siRNA-mediated knockdown of SPAK expression significantly reduced BK protein expression and increased ERK1/2 phosphorylation, whereas overexpression of SPAK significantly enhanced BK expression and decreased ERK1/2 phosphorylation in a dose-dependent manner. Knockdown of ERK1/2 prevented SPAK siRNA-mediated inhibition of BK expression. Similarly, pretreatment of HEK293 cells with either the lysosomal inhibitor bafilomycin A1 or proteasomal inhibitor MG132, reversed the inhibitory effects of SPAK knockdown on BK expression. We also found that there is no BK channel activity in PCs of CCD in SPAK KO mice using the isolated split-open tubule single cell patching. In addition, we found that BK protein abundance in the kidney of SPAK knockout mice was significantly decreased and ERK1/2 phosphorylation was significantly enhanced. A high potassium diet significantly increased BK protein abundance and SPAK phosphorylation levels, while reducing ERK1/2 phosphorylation levels. These findings suggest that SPAK enhances BK protein expression by reducing ERK1/2 signaling-mediated lysosomal and proteasomal degradations of the BK channel.